PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ELANG LABUAN MURNI JAKARTA BARAT - Innayah Ramadhanti, Desti; Gandung, Muhammad (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to find out the effect of compensation and work discipline on the performance of PT Elang Labuan Murni West Jakarta employees. This type of research is a quantitative type of research using associative methods. The data collection technique using the questionnairel method, the population in this study was all employees of PT Elang Labuan Murni, namely 63 employees using saturated samples. The data analysis techniques in this study are statistical analysis using validity test, reliability test, classical assumption test, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient determination test, hypothesis test and f hypothesis tests. The results of compensation research and work discipline on employee performance at PT Elang Labuan Murni West Jakarta are shown by the multiple linear regression equation Y = 6.208 + 0.432 X1 + 0.434 X2. This is evidenced by the simultaneous hypothesis test results obtained by the F-value of the table or 44.664 > 3.15 and strengthened by the significance value of 0.000 < 0.05. The results of the coefficient of determination of the compensation variable (X1) and work discipline (X2) test have an effect of 59.8% on the performance of employees at PT Elang Labuan Murni, West Jakarta. Thus H0 was rejected and H3 was accepted. This means that there has been proven to be a significant simultaneous effect between compensation (X1) and work discipline (X2) on employee performance (Y).